2022
DOI: 10.15678/eber.2022.100308
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of social media influencers on customers’ purchase intention: A sequential mediation model in Taiwan context

Abstract: The objective of the article is to investigate the impact of social media influencers (SMI) on Taiwanese customers' intent to buy, using sequential mediating effects of parasocial interaction, perceived value, and brand image. Research Design & Methods:The study focused on Taiwan and 384 samples were gathered using a convenience-based sampling technique. Variance-based structural equation modelling (SEM) was used to evaluate the sequential mediating effects through Smart PLS 3.0 statistical software. Findings:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Hypotheses H3g and H3h claimed that loyalty has a positive effect on purchase intentions (H3g) and attitude (H3h). The prior literature suggests positive effects for both relationships (Hussain and Ali 2021;Kanwar and Huang 2022;Ki et al 2020). Our study confirmed a positive and strong relationship between loyalty and purchase intention.…”
Section: Discussionsupporting
confidence: 86%
“…Hypotheses H3g and H3h claimed that loyalty has a positive effect on purchase intentions (H3g) and attitude (H3h). The prior literature suggests positive effects for both relationships (Hussain and Ali 2021;Kanwar and Huang 2022;Ki et al 2020). Our study confirmed a positive and strong relationship between loyalty and purchase intention.…”
Section: Discussionsupporting
confidence: 86%
“…A study shows that similarities between bloggers and readers can positively influence blog reader engagement and the intention to buy recommended products (Gomes et al, 2022;Magano et al, 2022). Other studies show a significant effect of similarity on purchase intention (Kanwar & Huang, 2022; J. K. Lee, 2021;Magno, 2017;Santiago Joanna K. et al, 2020). Therefore, the authors will raise the similarity hypothesis that influencers positively affect purchase intention.…”
Section: Similarity and Purchase Intentionmentioning
confidence: 97%
“…Perceived quality positively influences purchase intentions (Kanwar and Huang, 2022). In food retailing, Treiblmaier and Garaus (2023) reported the mediating role of product quality perceptions between the traceability of food product labels (as a quality signal) and purchase intentions.…”
Section: Purchase and Recommendation Intentionsmentioning
confidence: 98%